"Solve for x:" 2 X 3^2x+3 = 3 X 2^3x+4 (X is multiply) feel silly for posting this, is a simple log question i think, but its got me stumped. thanks
Follow Math Help Forum on Facebook and Google+
Just to clarify, you want to solve Is that correct? If so, what steps have you taken?
it could be also: in which case
sorry yeah the above is the way it's laid out - how did you get -1 ?
well several ways to solve this.. but you can divide both sides by and to elimate the coeficients, then after calculation we are left with
Last edited by bigwave; July 15th 2010 at 02:05 PM. Reason: added steps
ahhh it's so simple, i'm so stupid. haha thanks, i just didn't start with the basic, "dividng by 2" part. oops.
2(3)^2x+3 = 3(2)^3x+4 log 2 × log 3^(2x+3) = log 3 × log 2^(3x+4) (2x+3) log 3 = log 3 (3x+4) log 2 = log 2 2x log 3 + 3 log = log 3 2x log 3 = log 3 - 3 log 3 x(2 log 3) = -2 log 3 x = -2 log 3 /2 log 3 x = -1
View Tag Cloud